The Effect of Using Fiki Naki’s Youtube Content on Students’ Writing Skill at Eighth Grade of SMP GKPI Pamen Padang Bulan - Gaol, Fenny Gusrini Lumban; Tampubolon, Sahlan; Sidabutar, Usman (Lembaga Riset Mutiara Akbar, 2025)
This study aims to find out the types of errors are found on the uses youtube content in writing text at the eighth grade of SMP GKP Pamen Padang Bulan find out the dominant students' errors on the use video from youtube to see the effect in writing skill. There is phenomena in this research that is almost every student struggle with past forms errors when learning English. To achieve the objectives of this study, the researcher used a quantitative research design. The population of all eight grade students at SMP GKPI Pamen and the sample of this research there are 40 students. Technique of collecting data the researcher uses a test. To analyze the data involves four steps namely: identifying errors, describing error, summarize the findings the data. Based on the result findings of this research, the writer found there are There are 87 (36%) organize idea errors, 39 (19%) content error, 45 (21%) language error, 45 (21%) vocabulary errors, 8 (3%) mechanic errors of the eighth-grade students at SMP Pamen made several errors in the categories listed above. Based on the data, students to learn about the elements that contributed to the students' errors in using the youtube video in producing writing text. They struggle with parts of grammar in text and the overall structure and organize including problems they don't understand when compiling the writing text, etc.